The Workforce of Islamic Education Marketing Services at MTsN 1 Prabumulih - Destriyati, Destriyati; Ber, Zainal; za, Ahmad (The Future of Education Journal, 2024)
This research aims to analyze the role and strategy of marketing services workers in increasing competitiveness and attracting public interest in Islamic education, with a case study at MTsN 1 Prabumulih City. MTsN 1 Prabumulih City, as one of the leading madrasas with a number of students reaching 800 people, faces challenges in maintaining its existence amidst competition from other educational institutions. This research uses a qualitative-descriptive approach with data collection techniques through interviews, observation and document analysis.  The research results show that the marketing workforce at MTsN 1 Prabumulih City implements various strategies, such as promotion through social media, partnerships with local communities, organizing promotional events, and improving image through student achievements. However, challenges such as limited marketing budgets, competition with other schools, and changes in society's preferences for technology-based education are still the main obstacles. To overcome this, it is recommended to strengthen branding, optimize digital media, involve alumni as promotional ambassadors, and innovate technology-based learning programs. This research concludes that marketing services workers have a strategic role in improving the image and sustainability of Islamic educational institutions. The implication of this research is the importance of collaboration between marketing personnel, educators and management to develop more effective and sustainable promotional strategies.